Performance Optimization Of A Java Virtual Machine On Multi-Core Technology For Web Services - Chong, Kam Mun (2009)
The web server application is rapidly gaining importance in delivering services such as the online banking system provided by the financial instituition. This is due to the flexibility of the application for providing a large amount of processed information to the internet users via the network in an orderly manner. The connection of client and server using the Hyper-Text Transfer Protocol is one of the common standards where the web service model is implemented.